Penguatan Solidaritas dan Ketahanan Pangan: Bakti Sosial untuk Masyarakat Desa Tlogosari, Kecamatan Donomulyo Kabupaten Malang - Elvianto Wihatno; Doxana Putri Parahita (Universitas 45 Surabaya, 2024)
The social service activity held in Tlogosari Village, Donomulyo District, Malang Regency, on September 17, 2024, aims to strengthen social solidarity and food security among the local community. The program was organized by lecturers of the Institute of Science and Health Technology dr. Soepraoen Hospital Malang in collaboration with the Kartika Husada Clinic Donomulyo. The focus of the activity was to provide basic food assistance to underprivileged communities and orphans at the “Nasional Ayu” Orphanage, as well as moral support to them. In addition to providing material assistance, the lecturers also interacted directly with the community, providing motivation and support to the orphans to continue pursuing their education. This activity not only aims to ease the economic burden of the community, but also strengthens the relationship between educational institutions, healthcare facilities, and local communities. Good collaboration between academics, health workers, and the community shows a positive impact on the community's welfare through increased awareness of the importance of mutual cooperation and social care.